Report of the FAO expert workshop on the use of wild fish and/ or other aquatic species as feed in aquaculture and its implications to food security and poverty alleviation : (Food and Agriculture Organization of the United Nations, 2008)
The workshop consisted of technical presentations and working group discussions. The technical presentations included regional reviews, case studies, a global synthesis and a number of invited presentations. The workshop served to address various thematic areas and other issues of significance emerging from the regional reviews and case studies: fisheries management, policy development, food security, poverty alleviation, social and ethical issues, aquaculture technology and development.